Tendon incontinence repair: first experience with an autologous semitendinosus tendon transplant for urinary stress incontinence treatment - Hornemann, Amadeus; Hoch, Benjamin; Franz, Wolfgang; Sütterlin, Marc (Urology Case Reports, 2020)
In a 40-year-old caucasian patient with stress incontinence was a TVT operation performed with an autologous semitendinosus tendon transplant. The operation was done with spinal anesthesia. The tendon of the right musculus semitendinosus was stripped from the popliteal fossa and used instead of a synthetic tape as midurethral sling, as it is done in a classical retropubic TVT procedure. The operation was performed successfully. On the first day after the operation the transurethral catheter was removed, continence was reached, and no urinary retention was seen. Mobility and power of the affected leg did not change.